Responder
The solutions are \( m = 0 \), \( m = 1 \), and \( m = -2 \).
Solución
To solve the equation:
\[
4m^{3} + 4m^{2} - 8m = 0
\]
**Step 1: Factor out the Greatest Common Factor (GCF)**
First, identify and factor out the GCF from all terms. In this case, the GCF is \(4m\):
\[
4m(m^{2} + m - 2) = 0
\]
**Step 2: Apply the Zero Product Property**
The Zero Product Property states that if the product of multiple factors is zero, at least one of the factors must be zero. Therefore, set each factor equal to zero:
1. \(4m = 0\)
2. \(m^{2} + m - 2 = 0\)
**Solution for the First Factor:**
\[
4m = 0 \\
m = 0
\]
**Solution for the Quadratic Equation:**
\[
m^{2} + m - 2 = 0
\]
To solve the quadratic equation \(m^{2} + m - 2 = 0\), you can use the quadratic formula:
\[
m = \frac{-b \pm \sqrt{b^{2} - 4ac}}{2a}
\]
where \(a = 1\), \(b = 1\), and \(c = -2\).
Plugging in the values:
\[
m = \frac{-1 \pm \sqrt{(1)^2 - 4(1)(-2)}}{2(1)} \\
m = \frac{-1 \pm \sqrt{1 + 8}}{2} \\
m = \frac{-1 \pm \sqrt{9}}{2} \\
m = \frac{-1 \pm 3}{2}
\]
This gives two solutions:
1. \(m = \frac{-1 + 3}{2} = \frac{2}{2} = 1\)
2. \(m = \frac{-1 - 3}{2} = \frac{-4}{2} = -2\)
**Final Solutions:**
\[
m = 0, \quad m = 1, \quad \text{and} \quad m = -2
\]
**Verification:**
It's always good practice to verify the solutions by substituting them back into the original equation.
1. **For \(m = 0\):**
\[
4(0)^3 + 4(0)^2 - 8(0) = 0 + 0 - 0 = 0
\]
2. **For \(m = 1\):**
\[
4(1)^3 + 4(1)^2 - 8(1) = 4 + 4 - 8 = 0
\]
3. **For \(m = -2\):**
\[
4(-2)^3 + 4(-2)^2 - 8(-2) = 4(-8) + 4(4) + 16 = -32 + 16 + 16 = 0
\]
All solutions satisfy the original equation.
**Conclusion:**
The solutions to the equation \(4m^{3} + 4m^{2} - 8m = 0\) are:
\[
m = 0, \quad m = 1, \quad \text{and} \quad m = -2
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución